(untitled) (American Journal of Islam and Society, 2015)
Al-Ghazali (Abu Hamid Muhammad ibn Muhammad al-Tusi al-Ghazali, 1058-1111) is one of the most important thinkers in the history of Islamic and Arabic thought. He lived and wrote at the height of the intellectual ferment of Islam. Originally from Tus (in modern day Iran), he traveled extensively throughout the Muslim world. Al-Ghazali was a leading religious intellectual during his lifetime; he was a jurist (faqīh), a theologian (mutakallim), as well as a Sufi. Three of his most famous works are: The Incoherence of the Philosophers, Deliverer from Error, and Revivification of the Religious Sciences. The first work contains al-Ghazali’s famous and devastating attack on philosophy, and while it deals in large measure with theology and theological claims, it is principally a refutative work. In this book, al-Ghazali investigates philosophical doctrines and criticizes philosophers for holding many heretical opinions, especially for three blasphemous views that are deserving of death: the belief in the pre-eternity of the world (in effect denying God’s creation of the world), the denial of God’s knowledge of particulars, and the denial of the resurrection of bodies and their assembly at the Day of Judgment. This work is largely ...